Financial flows and exchange rates: Challenges faced by developing countries - Raquel Almeida Ramos (International Policy Centre for Inclusive Growth (IPC-IG), 2012)
[Introduction ...] This paper examines the problems of the excessive volatility of capital inflows in emerging market countries and its consequences on their exchange rates. The second section looks at the pattern of capital flows received by these countries, and the third section focuses on exchange rates. It first analyses the theoretical debate on setting exchange rates: the growing importance of financial flows on determining them, and whether it could be seen as a market-clearing price. Then it presents the links through which the exchange rate affects an economy, focusing on the specificities of developing countries which amplify these impacts. Later it discusses the changes seen in developing countries' choices of exchange rate regimes in light of the new pattern of capital flows. The fourth section analyses these issues during the global financial crisis.
Keywords: 330; Kapitalmobilität; Kapitalimport; Volatilität; Wechselkurs; Entwicklungsländer